Musik som språk - Hermerén, Göran (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1986)
The main purpose of this paper is to discuss the idea that music is a language and to focus on the analogies between verbal, visual and musical communication. The author is critical of these analogies and tries to call attention to some problems in the underlying conceptions of what a language is. Seven conditions for something to be a communicative language are formulated and the extent to which they are satisfied by musical compositions is discussed. Such compositions can be classified in several ways, and the distinctions between “program-music”, “descriptive music” and “abstract music” are discussed. The views of some recent musical cognitivists are mentioned, and one of them is singled out for critical analysis: Jerrold Levinson’s ideas about corresponding truths in music and propositional truths in music.